Analysis of The Effect of Education, Health And Dependent Burden on People's Purchasing Power In Medan City - Zendrato, Feronika; Parulian, Daniel Dohar; Ruslan, Dede (Journal of Community Research and Service, 2024)
This study aims to determine the influence of education, health, and dependents on the purchasing power of people in Medan City. The data used were primary data through questionnaires distributed to 100 families. The data were analyzed using multiple linear regression equations, t tests, F tests and regression coefficients with data processing using e-view 12. The results obtained y = 11.313 + 1.422X1 + 2.016X2 + 4.546X3, if education, health, dependent expenses remain then people's household consumption is in a fixed state or there is no change , of 11,313 items of staple goods. Based on the value of the t test and f test, it is obtained that education, health, dependent expenses have a significant effect on the purchasing power of the people in the city of Medan. The test result of the coefficient of determination 2 (R-Square) is 0.988 or 98.8%, while the remaining 1.2% is influenced by other variables.